2021
DOI: 10.1097/md.0000000000023684
|View full text |Cite
|
Sign up to set email alerts
|

Impact of music on anxiety and pain control during extracorporeal shockwave lithotripsy

Abstract: Background: The present evidence is insufficient for evaluating the impact of exclusive music therapy on anxiety and pain control in extracorporeal shock wave lithotripsy (ESWL). Methods: A systematic review and meta-analysis was conducted to explore the efficacy of music therapy in reducing pain and anxiety in patients undergoing ESWL. PubMed, Web of Science, Embase, EBSCO, and Cochrane library databases (updated March 2020) were searched for randomized controlled tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
(20 reference statements)
0
8
0
Order By: Relevance
“…The mean difference of pain scores between the music and control group in the 5 RCTs was 0.90, 0.50, 0.60, 2.00 & 2.00 (all showing significant reduction in pain with music). Similarly mean difference of anxiety scores between the music and control group in these RCTs was 3.30, 4.20, 4.20, 2.70 & 3.31 (again showing reduced anxiety with the use of music) 21 .…”
Section: Discussionmentioning
confidence: 60%
“…The mean difference of pain scores between the music and control group in the 5 RCTs was 0.90, 0.50, 0.60, 2.00 & 2.00 (all showing significant reduction in pain with music). Similarly mean difference of anxiety scores between the music and control group in these RCTs was 3.30, 4.20, 4.20, 2.70 & 3.31 (again showing reduced anxiety with the use of music) 21 .…”
Section: Discussionmentioning
confidence: 60%
“…The lithotripsy operator may also reduce the device's frequency and voltage due to the patient's unbearable and severe pain, resulting in a proportional decrease in lithotripsy success [ 35 ]. The most commonly used drug regimens for this purpose include NSAIDs such as diclofenac [ 36 ], sodium parecoxib [ 21 ], and opioids such as morphine [ 2 ]. However, the use of these drugs may be associated with several adverse effects: reduced renal blood flow, renal failure, severe nausea, vomiting, and potentially dangerous complications like respiratory depression, in addition to their high costs [ 10 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Urinary stones are one of the most common reasons individuals seek urology clinics [ 1 ], affecting 12% of the general population [ 2 ]. Extracorporeal shock wave lithotripsy (ESWL), a non-invasive therapeutic technique using shock waves, is considered the standard treatment for upper urinary tract and kidney stones [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have investigated the effect of music on pain reduction during SWL. A meta-analysis by Wang et al analyzed the results of 5 randomized controlled trials involving a total of 580 participants [5]. The meta-analysis found that music therapy signi cantly reduced pain intensity during SWL (Standardized mean difference = -1.20, 95% CI -1.95 to -0.45).…”
Section: Discussionmentioning
confidence: 99%